(untitled) (Research, Society and Development, 2022)
COVID-19 and its control constitute an example of a complex system, and most humans are poorly prepared to deal with complex systems. Here we show that government, some scientists and part of the news media did not recognize or ignored data that were freely available about the course of the epidemic in Brazil, and that this led to false conclusions and fatal decisions. The second wave of mortality did not originate in Manaus; Christmas and New Year celebrations that occurred long after the second wave started were not its primary cause; and social distancing accelerated rather than retarded the onset of the second wave. Had these facts been appreciated earlier, it would have been obvious that the only viable strategies were to reinforce the health system and obtain vaccines at any cost, and this might have saved between a quarter and half a million lives.